Application of Glucomannan - Sonia Sharma; Neeraj Wadhwa (Journal of Pharmaceutical Research, 2022)
Glucomannan (GM) a water-soluble polysaccharide possesses mannose residues which are extracted from tubers, bulbs, softwoods and roots of many plants. Glucomannan is considered to be a dietary fibre which is actually present in some plant species in the form of hemicelluloses component in the cell wall. Its structure consists of linear chain of mixed residues of α-1,4 linked D-mannose and D-glucose monomers arranged in blocks. The molecular weight of native GM lies between 1×104– 2×106. Low molecular weight GM could be obtained by de-polymerization technique. The average molecular weight of Konjac Glucomannan (KGM) is 500,000 – 2,000,000 and varies with species, growing area, storage time and processing methods. The glucomannan from different sources vary in its mannose to glucose ratio. Konjac tuber glucomannan has a molar ratio of 1.6:1 or 1.4:1 (ratio differs with konjac breeds), Orchid tubers and Scotch pine have molar ratios of 3.6:1 and 2.1:1 respectively. Diversity of glucomannan also depends on degree of acetylation in GM chain. Values of degree of acetylation are 5to10% or every 19th sugar residue (attached randomly at C-6 position in KGM), is actually responsible to facilitate dispersion and solubility by inhibiting the intra-molecular hydrogen bonds. This solubility function is attractive for multiple pharmaceutical applications. However increase in acetylation degree in GM slows the gelation process. The intrinsic viscosity of KGM solution is highest among the polysaccharides that facilitate swelling behaviour and hence gel formation that finds application in food industry. Gels have good stability, films, hydrogel, beads, micro and nanoparticles of Glucomannan may have potential usage in therapeutic drug delivery systems without causing toxicity. It may also be useful in treatment of chronic constipation, decreasing serum cholesterol, and increasing insulin sensitivity. As a food supplement it could play a significant role in weight loss. Carboxymethylated glucomannan improves the properties of paper, such as burst index, dry tensile index, and wet tensile index. These diverse applications make Glucomannan a most sought after biomolecule. Keywords: Biomolecule, Glucomannan, Diverse application